Residual Effect of Green Manure on the Growth and Yield of BRRI dhan28 - Islam, MR; Ryhana, Z; Hoque, MA; Huda, A; Begum, MLN (Journal of Environmental Science and Natural Resources, 2016)
Green manuring is a promising technology to enrich soils with organic matter especially with nitrogen to boost up rice production. An experiment was, therefore, conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2013 to evaluate the residual effect of Sesbania green manure on the growth and yield of BRRI dhan28. There were nine treatments laid out in a Randomized Complete Block Design (RCBD) with three replications. The results demonstrate that the treatment T8 containing 75% recommended dose of nitrogen (RDN) and green manure incorporated at 70 DAS produced the highest grain yield of 4967 kg ha-1 and straw yield of 5359 kg ha-1. The lowest grain yield (4208 kg ha-1) and straw yield (4352 kg ha-1) were recorded for the treatment T1 (GM incorporated at 40 DAS + 50% RD of NF). Green manure exerted significant residual effect on grain N uptake, straw N uptake and total N uptake of BRRI dhan28. The residual effect of green manure was the higher in producing rice yields in treatments with the application of 75% of recommended N fertilizer with green manure incorporated at 50 or 70 DAS. J. Environ. Sci. & Natural Resources, 9(1): 35-40 2016